Capital regulation and bank balance sheet adjustments: a simultaneous approach. (2nd June 2019) - Nguyen, Quang Thi Thieu; Gan, Christopher; Li, Zhaohua
Abstract: This study examines the balance sheets of banks in 15 Asian countries from 2004 to 2016 to explore how they respond to stricter capital regulation. We consider the simultaneity of balance sheet adjustments. Employing a normalisation method, the study found that Asian banks increased regulatory capital, primarily through retained earnings, and expanded assets over the study period. However, the two‐step system Generalised Method of Moments results do not support the positive effect of capital regulation on regulatory capital components adjustments. In addition, stricter capital regulation even induces banks to reduce lending.